What can public schools do about Early School Leaving? Exploring support measures for students through two case studies in Catalonia in a context of crisis - Carrasco, Sílvia; Narciso, Lai; Bertran, Marta (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
This paper presents some results of a qualitative research carried out in two public high schools with different sociocultural composition in Catalonia about the main support measures for students that can contribute in our education system to struggle against the high rate of Early School Leaving following the definition of the Lisbon Millennium Goals. In a context featured by the reduction of public investment in education, these measures are explored and analyzed within their conditions of implementation in schools and the risk and protective factors they entail, taking into account teachers’, students’ and families’ perspectives and perceptions. This piece of research is part of the comparative European Project Reducing Early School Leaving in Europe (RESL.eu) that investigates the mechanisms and processes pushing youth to leave formal education and training without post-compulsory academic or professional qualifications and intends to identify good practices that promote their school continuity in spite of being at risk of dropping out.